Malawi’de Merkez Bankası’nın bağımsızlığı ölçümü: yeni kurumsal kalıte endeksi - Kamanga, Frank (My University, 2017)
MALAWİ’DE MERKEZ BANKASI’NIN BAĞIMSIZLIĞI ÖLÇÜMÜ: YENİ KURUMSAL KALITE ENDEKSİ Bu araştırma Malavideki MBB’yi analiz ederek Kurumsal Kalite Endeksi metodolojisini uygulamıştır. Bu ilişkiler ekonomi yönetiminde devlet ve kamu idarelerinin rolünden hareket ederek, Yeni Kurumsal İktisadi çerçevesi içinde analiz ediliyor. Bu metot aynı zamanda Merkez bankasının bağımsızlığını güncel uygulamalar bazında değerlendirir. Uygulamada bankacılık yasalarının ağırlıklı olarak göz ardı edildiği gelişmekte olan ülkeler için uygun bir metodoloji olduğundan bu metotla hareket ettik. Metot, Merkez bankasının bağımsızlığını güncel uygulamalar bazında da değerlendirir. Araştırma Malavi için ortalama MBB endeksinin, toplam endeks olan 36’nin yarısından daha az olarak 15.1 olduğu sonucuna ulaştırmıştır. Bu durum Malavi Merkez Bankasının ikna edici bir biçimde bağımsız olmadığını açıkca göstermektedir. Para politikası bağımsızlık ortalamasının üstünde olmasına rağmen banka, siyasi ve mali bağımsızlığa sahip değildir. Son olarak ise çalışmamızda, En Küçük Kareler Yöntemi regresyon analizi kullanılarak, araştırma, Malavi Merkez Bankasının düşük bağımsızlık seviyesinin Malavi’deki enflasyona sebep olduğu sonucuna ulaşmıştır. Malavi Merkez Bankasının bağımsızlığı ve enflasyon arasındaki ilişkinin devlet ile yapılan işler ve devlet tahvili satın alımıyla ilgili olduğu tahmin edilmektedir. Kurumsal Kalite Endeksi, Malavi Merkez Bankası, Merkez Bankası Bağımsızlığı, Enflasyon

MEASURING CENTRAL BANK INDEPENDENCE IN MALAWI: THE NEW INDEX OF INSTITUTIONAL QUALITY APPROACH This study applied the Index of Institutional Quality (IQ) methodology to measure the level of independence of the Reserve Bank of Malawi (central bank) and examine its impact on inflation. The IQ methodology assesses independence of central banks based on their actual practices. The methodology is suitable for developing countries whose practices do not fully conform to the laws of Banks that are in place. The study finds that the average independence index of the Reserve Bank of Malawi (RBM) is 15.1, which is more than half below the total index value of 36. This clearly shows that the RBM is not convincingly independent. Although the results show an above-average value for index of monetary policy independence, indications are that the RBM is not free from political pressures as evidenced by below-average values for indices of political and fiscal independence. Using Ordinary Least Square (OLS), the results further show that the low degree of indepedence by the RBM has contributed to high inflation in Malawi. This study applied the Index of Institutional Quality (IQ) methodology to measure the level of independence of the Reserve Bank of Malawi (central bank) and examine its impact on inflation. The IQ methodology assesses independence of central banks based on their actual practices. The methodology is suitable for developing countries whose practices do not fully conform to the laws of Banks that are in place. The study finds that the average independence index of the Reserve Bank of Malawi (RBM) is 15.1, which is more than half below the total index value of 36. This clearly shows that the RBM is not convincingly independent. Although the results show an above-average value for index of monetary policy independence, indications are that the RBM is not free from political pressures as evidenced by below-average values for indices of political and fiscal independence. Using Ordinary Least Square (OLS), the results further show that the low degree of indepedence by the RBM has contributed to high inflation in Malawi.
Keywords: Ekonomik durum; Hukuk ve mevzuat; Malawi; Merkez Bankası